Two new Orthocladiinae (Diptera: Chironomidae) collected in overlooked places of Midwest USA - Namayandeh, Armin; Hudson, Patrick L. (Zootaxa, 2022)
We describe Cedrimyia margareti gen. nov., sp. nov. from Ohio and Wisconsin, and Parakiefferiella mishigami sp. nov. (Orthocladiinae) from Michigan. Cedrimyia is likely related to Antillocladius Sæther, 1981, Litocladius Mendes, Andersen and Sæther, 2004, Lyrocladius Mendes and Andersen, 2008, and Compterosmittia Sæther, 1981, genera with scalpellate acrostichals. The new species of Parakiefferiella has a well-separated bilobed inferior volsella differing in shape from known Parakiefferiella species.